Advancing Gender Equity in Higher Education Research - Nkosi, Ntombikayise; Maphalala, Mncedisi (African Journal of Inter/Multidisciplinary Studies, 2025)
Gender equity in research in higher education is crucial for promoting inclusivity and driving innovation. However, female academics face significant challenges hindering their research output, career advancement, and fair academic representation. Ongoing issues include heavy teaching responsibilities, time constraints, limited access to mentorship and supportive networks, and ingrained biases in institutional cultures. This study explores how universities can enhance gender equity in higher education research and identify the actions which institutions can take to support female academics and address the structural challenges they encounter. A systematic literature review (SLR), following PRISMA guidelines, was undertaken to consolidate peer-reviewed empirical studies published between 2013 and 2023. The articles were assessed for relevance, and a thematic analysis was employed to uncover common barriers and institutional strategies. The review identified systemic and institutional obstacles, such as unequal workload distribution, limited funding opportunities, and insufficient mentorship, as significant barriers to women’s research productivity. However, the study also highlights the potential of effective interventions such as gender-sensitive policies, mentorship programmes, leadership development initiatives and equitable research funding mechanisms to foster inclusive academic environments and reduce gender disparities. The study highlights the need for higher education institutions to adopt transformative and systemic strategies that promote gender equity in research. Recommendations include implementing gender-responsive policies, targeted funding initiatives and well-structured mentorship programmes to eliminate the obstacles faced by female academics. This study recommends creating supportive environments that foster women’s success in academia. It addresses knowledge gaps through research and thematic trends to inform future research and drive institutional change.